1990
DOI: 10.1161/01.atv.10.5.732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary magnesium on development of atherosclerosis in cholesterol-fed rabbits.

Abstract: The effect of dietary magnesium (Mg) on the development of atherosclerosis In cholesterol-fed rabbits was investigated. Male New Zealand White rabbits (n=31) were placed on five kinds of diets: regular, 1% cholesterol, and 1% cholesterol diets supplemented with either 300, 600, or 900 mg (as Mg) of Mg sulfate. The regular and 1% cholesterol diets contained 400 mg of Mg per 100 g. Each rabbit received 100 g daily of the appropriate diet Additional Mg was well tolerated and did not affect blood pressure or body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 27 publications
6
47
0
1
Order By: Relevance
“…In the blood chemical values, TG level was significantly higher in the 6.7% dSSW group, while no significant differences in TC, HDLC, and GLU were found among the 7 water groups. Inverse association between magnesium intake and plasma TG level has been previously reported (Altura et al 1990;Ouchi et al 1990;Sherer et al 1999;Ravn et al 2001;Cohen et al 2002). As shown in Table 1, dDSW and dSSW are rich in calcium and magnesium.…”
Section: Discussionsupporting
confidence: 53%
“…In the blood chemical values, TG level was significantly higher in the 6.7% dSSW group, while no significant differences in TC, HDLC, and GLU were found among the 7 water groups. Inverse association between magnesium intake and plasma TG level has been previously reported (Altura et al 1990;Ouchi et al 1990;Sherer et al 1999;Ravn et al 2001;Cohen et al 2002). As shown in Table 1, dDSW and dSSW are rich in calcium and magnesium.…”
Section: Discussionsupporting
confidence: 53%
“…Simple linear regression demonstrated positive relationship of urinary K to SBP and DBP in JJ-men and of urinary Na/K ratio to DBP in JB-men, but these relationships disappeared when multiple linear regression was applied. Beneficial effects of Mg and K on BP were unclear in this study, despite several investigations showing an antihypertensive effect (9-11, 55,56,62,63) JJ had 1.5-2 times higher urinary taurine (TAU) excretion than JB. Urinary TAU related positively with DBP at the individual level in JJ-women in simple linear regression analysis, but its independent effect on BP was unclear in multiple linear regression analysis controlling for other confounding factors.…”
Section: Discussionmentioning
confidence: 62%
“…24,25 Increased Mg intake was suggested to counteract these effects in animal models. 26,27 Epidemiological studies have indicated a direct relation between atherosclerosis and low serum Mg, 3,6 -10 which, in turn, depends on dietary intake. A direct relation between serum Mg levels and acute neurological events has not yet been described.…”
Section: Amighi Et Al Magnesium and Neurological Events 25mentioning
confidence: 99%